A comparative study of the quality of the managers, teachers and facilities of private and public primary schools in Ibadan, Oyo state. (2005)
This paper compared the quality of private and public schools in ibadan in Oyo state. The sample for the study comprised 15 randomly selected schools of each type across five of the eleven local government areas that make up Ibadan. The findings of the study were that the management, at tha personal management characteristics level, in the public schools was more qualitative than in the private schools. In additon, the private schools performed better in the area of school-imposed indicaators of quality. There same findings were true of the teachers quality indices. These differences between the two types of schools on the aggregate were discovered to be significant in favour of public schools in the qualty of schools management and that of teachers whereas it was in favour of private schools in terms of the quality of infrastructure. However, neither of the two school tyoes had absolute edge over the other in any of the three quality variables of the study. Based on these findings, relevant recommendations were made for improvement of schools irrespective of ownership.